Effect of Intersection Angle of Input Channels in Droplet Generators - Gi-Beum Kim; Young-Ran Park; Seong-Jong Kim; Kwang-Hyun Park (Molecules, 2022)
In this paper, we studied the effects of the intersection angle between the inlet channels on the droplet diameter using a COMSOL Multiphysics® simulation. We employed the level-set method to study the droplet generation process inside a microfluidic flow device. A flow-focusing geometry was integrated into a microfluidics device and used to study droplet formation in liquid–liquid systems. Droplets formed by this flow-focusing technique are typically smaller than the upstream capillary tube and vary in size with the flow rates. Different intersection angles were modeled with a fixed width of continuous and dispersed channels, orifices, and expansion channels. Numerical simulations were performed using the incompressible Navier–Stokes equations for single-phase flow in various flow-focusing geometries. As a result of modeling, when the dispersed flow rate and the continuous flow rate were increased, the flow of the continuous flow fluid interfered with the flow of the dispersed flow fluid, which resulted in a decrease in the droplet diameter. Variations in the droplet diameter can be used to change the intersection angle and fluid flow rate. In addition, it was predicted that the smallest diameter droplet would be generated when the intersection angle was 90°.